The Role Of Account Receivables In Handling Delays In Billing Account (Invoices) At The Aruss Hotel Semarang - Fransisca Candra Sutrisno; A. Soerjowardhana (International Forum of Researchers and Lecturers, 2023)
This final project aims to explain the role of accounts receivable in handling delays in collection of receivables (invoices) at the Aruss Hotel Semarang. The data collection method used in this study is a study of secondary documents, so that accurate data can be obtained regarding the role of efforts to handle late collection of receivables. There are various causes for late payment of receivables, one of which is the length of time for disbursing funds so that payments exceed the due date given. The results that can be obtained from this study are that accounts receivable have an important role in maintaining hotel cash flow and overcoming delays in collecting receivables at the Aruss Hotel Semarang. Accounts receivable play an important role in maintaining the hotel's cash flow, one of which is to overcome how guests experience delays in paying. In addition, the role of other departments is no less important in collecting receivables from guests.